Inhibition of cardiac Kir2.1-2.3 channels by beta3 adrenoreceptor antagonist SR 59230A - Kulzer, Martin; Seyler, Claudia; Welke, Florian; Scherer, Daniel; Xynogalos, Panagiotis; Scholz, Eberhard P.; Thomas, Dierk; Becker, Rüdiger; Karle, Christoph; Katus, Hugo; Zitron, Edgar (Biochemical and biophysical research communications, 2012)
Kir2.x channels form the molecular basis of cardiac IK1 current and play a major role in cardiac electrophysiology. However, there is a substantial lack of selective Kir2 antagonists. We found the β3-adrenoceptor antagonist SR59230A to be an inhibitor of Kir2.x channels. Therefore, we characterized the effects of SR59230A on Kir2.x and other relevant cardiac potassium channels. Cloned channels were expressed in the Xenopus oocyte expression system and measured with the double-microelectrode voltage clamp technique. SR59230A inhibited homomeric Kir2.1 channels with an IC50 of 33μM. Homomeric Kir2.2 and Kir2.3 channels and Kir2.x heteromers were also inhibited by SR59230A with similar potency. In contrast, no relevant inhibitory effects of SR59230A were found in cardiac Kv1.5, Kv4.3 and KvLQT1/minK channels. In hERG channels, SR59230A only induced a weak inhibition at a high concentration. These findings establish SR59230A as a novel inhibitor of Kir2.1-2.3 channels with a favorable profile with respect to additional effects on other cardiac repolarizing potassium channels.